Analysis of the Effect of Management of Receivables Risk with Credit Scoring on Credit Collectibility - Tsania Nur Salima; Mukaram (Ebiz Prima Nusa, 2024)
A good management of account receivable is needed to encourage company revenues to be able to fulfill financing needs. One way to manage receivables is to do credit scoring. This research was conducted to examine the effect, direction, and significance of credit scoring on credit collectability at PT Krakatau Steel in 2022 to 2023. In this study, the data used is secondary data, obtained from company archives. The population of this study is all consumers registered in the company, namely as many as 709 companies. The number of samples taken was 228 samples with the criteria of consumers who are still making transactions from 2022 to 2023. The results obtained using descriptive analysis show that credit scoring is in the good category and the company's credit collection is in the current category. Credit scoring has a positive and significant effect of 74.2% on credit collectability at PT Krakatau Steel with a significance level of 0.000.